RELIGIOUS PLURALISM, MULTI-ETHNIC NATIONALIST IDENTITY, AND THE SIGNIFICANT CONTRIBUTION OF ISLAMIC PRINCIPLES - Mahbub, Moh. Azizi Al (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Religious pluralism is a new form of religious consciousness, and a potential for renewing theology, especially since it is based on the principle of interreligious dialogue. In this article, we will discuss the definition of religion, Western views on religion, multi-ethnic nationalist identities, and Islamic attitudes towards religion. We will also discuss the principles and fundamentals underlying this Islamic stance. The method used in this research is qualitative research through library research